Pengembangan Model Blended Learning Berbasis Google Classroom Pada Mata Kuliah Rekayasa Sistem Audio - Supriadi Supriadi; Mahmud Mustafa (Seminar Nasional LP2M UNM, 2019)
Abstract. The purpose of this study was to determine the development and feasibility of a google classroom-based Blended Learning model in the Audio System Engineering course in the Department of Electronics Engineering FT-UNM. This research is a research and development of Research and Dependency (R&D). According to Punaji Setyosari (2010: 230), states that research development is a process used to develop and validate educational products. The development of the Google classroom-based blended learning model follows the stages of the development of an educational design model from Plomp. Plomp shows that a model in designing education (including learning) consists of 5 (five) stages, namely the initial investigation stage, the design / design stage, the realization / construction stage, the test phase, evaluation and revision & implementation stage. Based on these steps, then combined with the elements of the development of learning models proposed by Joyce & Weil, the model of developing learning material (products) by Nieveen, and the instructional system development model by Dick & Carey. The feasibility of a google classroom-based blended learning model in the Audio System Engineering course that has been developed is declared